1989
DOI: 10.1111/j.1151-2916.1989.tb09724.x
|View full text |Cite
|
Sign up to set email alerts
|

Precise Nondestructive Determination of the Density of Porous Ceramics

Abstract: A fast, accurate, inexpensive, and nondestructive method to determine the density of very porous ceramics has been found. This method is an extension of the water-displacement technique with three weighings and the use of glycerol instead of water. For small (1 .I3 g ) , 29% porosity B,C pellets, the precision is 0.002 glcm' and the accuracy is better than 0.006 g/cm' compared with the geometric density. [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
4

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 1 publication
0
18
0
4
Order By: Relevance
“…A porosidade aberta e a densidade hidrostática foram medidas em tréplica pelo método de ARTHUR [12] nos compósitos sinterizados contendo a maior concentração de precursor minoritário. O procedimento consiste em pesar o corpo de prova seco ao ar em gramas (M I ).…”
Section: Porosidade Aberta E Densidade Hidrostáticaunclassified
See 1 more Smart Citation
“…A porosidade aberta e a densidade hidrostática foram medidas em tréplica pelo método de ARTHUR [12] nos compósitos sinterizados contendo a maior concentração de precursor minoritário. O procedimento consiste em pesar o corpo de prova seco ao ar em gramas (M I ).…”
Section: Porosidade Aberta E Densidade Hidrostáticaunclassified
“…Portanto, a sinterização dos materiais inicia em temperaturas abaixo daquelas usadas na literatura para sinterizar compósitos à base de titânio contendo cálcio e fósforo, que foram entre 1000 e 1400 [12,16].…”
Section: Calorimetria Diferencial De Varredura (Dsc) E Termogravimetrunclassified
“…Characteristics of tubular porous ceramic supports were analyzed by the Archimedes test 35 . The results showed 48 % open porosity, 10 % closed porosity and 42 % relative density, which indicated that the porosity of the fabricated parts is appropriate.…”
Section: Silica Membrane Microstructuresmentioning
confidence: 99%
“…The surfaces of the pellets produced by hot pressing were ground to remove any graphite and carbide layers formqd during heating. Pellet densities were then measured using the Archimedes' Method (see, e.g., [12]) and the results are shown in Table I. based on ultrasonic excitation and measurement of the mechanical resonant frequencies of a small sample having a regular shape [13].…”
Section: Introductionmentioning
confidence: 99%